Late Pleistocene vertebrate trace fossils of the Walker Bay Nature Reserve - Helm, Charles W.; Carr, Andrew S.; Cawthra, Hayley C.; De Vynck, Jan C. (The Evolutionary Studies Institute, 2024)
In the Walker Bay Nature Reserve, on South Africa’s Cape southwest coast, a suite of 25 Pleistocene ichnosites has been identified in aeolianite deposits. Dating from one site using optically stimulated luminescence indicates an age of 76 ± 5 ka. Highlights, indicating the global importance of the reserve, include a possible hominin tracksite and the first reported occurrence of fossil snake traces and tortoise tracks. The ichnological findings can be correlated with the substantial archaeological record from the nearby DieKelders Cave. Elephant tracks are reported from several sites, but are not present in the archaeological record, whereas the plentiful occurrence of burrow traces of appropriate size corroborates the body fossil record from archaeological deposits, in which the Cape dune molerat predominates. The protected nature of the region allows for opportunities for conservation and education. Photogrammetry represents a non-invasive means of preserving and replicating the ichnological findings.
Keywords: Late Pleistocene; aeolianites; hominin tracks; snake traces; burrow traces; OSL dating; SDG-13: Climate action